1975
DOI: 10.1111/j.1600-051x.1975.tb01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of occlusal adjustment by grinding on gingivitis and mobility of traumatized teeth

Abstract: The effect on marginal inflammation and tooth mobility of occlusal adjustment by grinding was investigated in 43 occlusally traumatized teeth in 29 subjects with gingivitis and marginal periodontitis. The material consisted of 4 groups with tooth mobility of varying degrees of severity, and bone destruction. In all groups increased tooth mobility decreased subsequent to occlusal adjustment. The latter was without effect on the sulcus fluid flow rate or gingivitis scores in either gingivitis or periodontitis pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1976
1976
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…The rather crude method of measuring the mobility of the Test Teeth in this study did not reveal changes in the short period of 28 d. But the jiggling in conjunction with movements of the jaw was reduced or eliminated from the Test Tooth by occlusal adjustment. It has been suggested that the jiggling of the traumatized tooth enhances the inflammatory reaction in the periodontium by a "pumping action" (27).…”
Section: Discussionmentioning
confidence: 99%
“…The rather crude method of measuring the mobility of the Test Teeth in this study did not reveal changes in the short period of 28 d. But the jiggling in conjunction with movements of the jaw was reduced or eliminated from the Test Tooth by occlusal adjustment. It has been suggested that the jiggling of the traumatized tooth enhances the inflammatory reaction in the periodontium by a "pumping action" (27).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was no obvious difl'erence between mean scores for the subjects and for the test teeth, indicating that the choice of the lower left first molar was a representative one. The efl'ect of increased tooth mobility in the presence of occlusal traumatism has been demonstrated (Vollmer & Rateitschak, 1975). However, despite the presence of occlusal discrepancies, which in some cases were marked, in all the subjects, tooth mobility was negligible.…”
Section: Discussionmentioning
confidence: 96%
“…These effects are reversible. Eliciting occlusally traumatogenic factors are eliminated by grinding and the resultant pathological mobility is decreased within 7 days (Renggli & Muhlemann 1970, Vollmer & Rateitschak 1975.…”
Section: Discussionmentioning
confidence: 99%